2016
DOI: 10.1021/acs.jchemed.5b00830
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Students to Gas Chromatography–Mass Spectrometry Analysis and Determination of Kerosene Components in a Complex Mixture

Abstract: Gas chromatography−mass spectrometry (GC−MS) and GC−tandem MS (GC−MS/MS) are useful in many separation and characterization procedures. GC−MS is now a common tool in industry and research, and increasingly, GC−MS/ MS is applied to the measurement of trace components in complex mixtures. This report describes an upper-level undergraduate experiment to understand aspects of GC−MS analysis for a mixture of compounds, carry out a protocol for selected ion monitoring, and then determine a number of kerosene compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Experience of these practical analytical procedures is useful in academia, government, and industry. Laboratory experiments on the use of chromatography (gas and liquid)–mass spectrometry-based methods with applications in the chemical, , environmental, forensic, biological, and clinical fields are being taught at the universities, but additional training and hands-on experience in these methods should be available in the analytical chemistry and instrumental analysis laboratory courses to provide invaluable skills and experience for undergraduate students.…”
Section: Resultsmentioning
confidence: 99%
“…Experience of these practical analytical procedures is useful in academia, government, and industry. Laboratory experiments on the use of chromatography (gas and liquid)–mass spectrometry-based methods with applications in the chemical, , environmental, forensic, biological, and clinical fields are being taught at the universities, but additional training and hands-on experience in these methods should be available in the analytical chemistry and instrumental analysis laboratory courses to provide invaluable skills and experience for undergraduate students.…”
Section: Resultsmentioning
confidence: 99%
“…In future years, we recommend an in-class activity prior to the lab exercise that has students analyze such complex mixture data by comparing retention times and ionization spectra, similar to ways in which we teach NMR, 33−35 or as Pacot et al recently suggested, through first analyzing a set of data from a standard mixture. 36 Classroom discussions and free-response surveys demonstrated that students gained an appreciation for the inherently complex nature of pollutant mixtures, and the potential risks posed at what students first think are "small" (ppm) concentrations. Said one student: "Even small concentrations of many of the PAHs found in this experiment have health risks... detection and regulation of even small amounts through quantitative analysis is important to ensure the health and safety of our water sources, crops, and the environment..."…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This was the students’ first exposure to the analysis of complex mixtures via GC–MS, and they were initially overwhelmed by the myriad peaks on the chromatograms. In future years, we recommend an in-class activity prior to the lab exercise that has students analyze such complex mixture data by comparing retention times and ionization spectra, similar to ways in which we teach NMR, or as Pacot et al recently suggested, through first analyzing a set of data from a standard mixture …”
Section: Assessment Implications and Limitationsmentioning
confidence: 99%
“…GC–MS is one of the most useful methods for quantitatively and qualitatively identifying sample constituents. The technique allows separating volatile components with good selectivity and sensitivity and provides structural information about compounds. …”
Section: Introductionmentioning
confidence: 99%
“…The proposed experiment has the following strengths: it can be carried out in a short period, contributes to a better understanding of the theoretical concepts of GC–MS, and encourages students to use scientific research to propose solutions for real environmental problems. …”
Section: Introductionmentioning
confidence: 99%